2014
DOI: 10.1104/pp.113.232090
|View full text |Cite
|
Sign up to set email alerts
|

Using a Viral Vector to Reveal the Role of MicroRNA159 in Disease Symptom Induction by a Severe Strain of Cucumber mosaic virus

Abstract: In transgenic Arabidopsis (Arabidopsis thaliana), expression of the Cucumber mosaic virus (CMV) 2b silencing suppressor protein from the severe subgroup IA strain Fny disrupted microRNA (miRNA)-regulated development but orthologs from mild subgroup II strains (Q and LS) did not, explaining strain-specific differences in symptom severity. However, it is unknown which miRNAs affected by Fny2b critically affect viral symptoms. Observations that Fny2b-transgenic plants phenocopy microRNA159ab (mir159ab) mutant pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 59 publications
0
59
0
Order By: Relevance
“…Then, plants have evolved sophisticated mechanisms to defend such stresses (Galvez et al, 2014). Recently, miRNAs have turned out to be regulons in plant tolerance to abiotic and biotic stresses like cold, drought, heat, fungi and virus (Taylor et al, 2014), and much effort has been devoted to understanding their role in the responses of viral disease in various plants including: wheat (Fahim et al, 2010), tomato (Feng et al, 2014), cucumber (Du et al, 2014), grape (Miozzi et al, 2013) and rice (Guo et al, 2012). In the present study, deep sequencing technology was used for quantitative determination of genome-wide miRNA expression patterns of non-heading Chinese cabbage in response to TuMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Then, plants have evolved sophisticated mechanisms to defend such stresses (Galvez et al, 2014). Recently, miRNAs have turned out to be regulons in plant tolerance to abiotic and biotic stresses like cold, drought, heat, fungi and virus (Taylor et al, 2014), and much effort has been devoted to understanding their role in the responses of viral disease in various plants including: wheat (Fahim et al, 2010), tomato (Feng et al, 2014), cucumber (Du et al, 2014), grape (Miozzi et al, 2013) and rice (Guo et al, 2012). In the present study, deep sequencing technology was used for quantitative determination of genome-wide miRNA expression patterns of non-heading Chinese cabbage in response to TuMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic Arabidopsis overexpressing a miR159-resistant MYB33 that contained mutated miRNA-target sequence developed curled-up and round leaves (Millar and Gubler 2005). Recent research demonstrated that miR159 exacerbated viral symptoms through the depression of MYB33 and MYB65 in Arabidopsis (Du et al 2014). It appears that miR159 may be closely associated with disease symptoms, such as reduction of leaflet blades and delayed flowering time in CMV-infected tomato.…”
Section: Mirnas and Disease Symptomsmentioning
confidence: 96%
“…Moreover, the new CMV-HL vector was also preserved in dormant bulbs and spread into sprouting shoots in the following year (Figures 2 and 3). In CMV-derived viral vectors, the cloning sites of target genes are usually integrated at the downstream of 2b gene (Hong et al 2012;Kanazawa et al 2011;Otagaki et al 2006) and in only one instance the cloning site has been introduced downstream of the 3b gene (Du et al 2014). Therefore, the present study is the first to demonstrate that host plant gene fragments could be introduced just upstream of the 3b start codon without preventing systemic viral infection.…”
Section: Discussionmentioning
confidence: 90%